2019
DOI: 10.1111/nph.15722
|View full text |Cite
|
Sign up to set email alerts
|

How do arbuscular mycorrhizal fungi travel?

Abstract: This article is a Commentary on Correia et al., 222: 1054–1060.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Due to the long-distance dispersal limitation of arbuscular mycorrhizal fungi to the islands [10], an absence of mycorrhizal fungi on newly formed island land masses is likely. This would be expected to act as a filter as the establishment of plants that rely on these symbiotic interactions would be selected against, and therefore reduce the establishment of mycorrhizal dependent plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the long-distance dispersal limitation of arbuscular mycorrhizal fungi to the islands [10], an absence of mycorrhizal fungi on newly formed island land masses is likely. This would be expected to act as a filter as the establishment of plants that rely on these symbiotic interactions would be selected against, and therefore reduce the establishment of mycorrhizal dependent plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if large spores might limit dispersal at smaller (e.g. intra-continental) scales in AMF [22, 89], this does not seem to affect diversification.…”
Section: Discussionmentioning
confidence: 99%
“…A previous dated phylogenetic tree of AMF VT found that most origination times occurred after the last major continental reconfiguration around 100 Myr ago 18 , suggesting that AMF diversification is not linked to vicariant speciations during this geological event. Still, geographical speciation could play an important role in AMF diversification, as these organisms have spores that disperse efficiently over long distances [19][20][21] , which could result in frequent founder-event speciation 22 . Other abiotic factors include habitat: it has for example been suggested that tropical grasslands are diversification hotspots for AMF 23 .…”
Section: Introduction (500 Words)mentioning
confidence: 99%
“…Co-introduction is not a common pathway for plants and AMF. Production of fewer and bigger spores than EM fungi, and the comparatively limited extent of AMF mycelia are likely to limit the dispersal of these fungi across large geographic distances (Denison and Kiers 2011; Bueno and Moora 2019). For EM fungi, long-distance dispersal is known to occur via spores (Peay et al .…”
Section: Eco-evolutionary Experience Is Important For Mycorrhizal Andmentioning
confidence: 99%